C7N6 monolayer as high capacity and reversible hydrogen storage media: A DFT study. (18th June 2021) - Hu, Song; Yong, Yongliang; Zhao, Zijia; Gao, Ruilin; Zhou, Qingxiao; Kuang, Yanmin
Abstract: Searching advanced materials with high capacity and efficient reversibility for hydrogen storage is a key issue for the development of hydrogen energy. In this work, we studied systematically the hydrogen storage properties of the pure C7 N6 monolayer using density functional theory methods. Our results demonstrate that H2 molecules are spontaneously adsorbed on the C7 N6 monolayer with the average adsorption energy in the range of 0.187–0.202 eV. The interactions between H2 molecules and C7 N6 monolayer are of electrostatic nature. The gravimetric and volumetric hydrogen storage capacities of the C7 N6 monolayer are found to be 11.1 wt% and 169 g/L, respectively. High hardness and low electrophilicity provides the stabilities of H2 –C7 N6 systems. The hydrogenation/dehydrogenation (desorption) temperature is predicted to be 239 K. The desorption temperatures and desorption capacity of H2 under practical conditions further reveal that the C7 N6 monolayer could operate as reversible hydrogen storage media. Our results thus indicate that the C7 N6 monolayer is a promising material with efficient, reversible, and high capacity for H2 storage under realistic conditions. Graphical abstract: Image 1 Highlights: Hydrogen storage properties of pure C7 N6 monolayer was studied using DFT method. C7 N6 monolayer stores 11.1 wt% H2 with ideal adsorption energies of 0.187–0.202 eV. Interactions between H2 molecules and C7 N6 monolayer are of electrostatic nature. High hardness and low electrophilicity provides the stabilities of H2 –C7 N6 systems. Desorption temperature and capacity verify the reversibility of H2 storage.